2015
DOI: 10.1051/matecconf/20153304002
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing martensite transitions in Fe-based shape memory alloys

Abstract: Abstract. Fe-14Mn-6Si-9Cr-5Ni (mass %) shape memory alloy (SMA) specimens were obtained by powder metallurgy in as-blended state (0_MA) and with particle volume fractions of 10 and 20 % MA'd powders, respectively. After hot rolling and solution treatment, between 973 and 1373 K, the specimens were pre-strained up to 4 %, on a tensile testing machine. The influences of: (i) MA'd fractions, (ii) solution treatment temperature and (iii) pre-straining degree were analysed by X-ray diffraction (XRD), optical (OM) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…On the other hand, the present authors pointed out that, in MA'ed Fe–Mn–Si–Cr–Ni SMAs, a second internal friction maximum occurs during heating. This tan δ maximum, located at a temperature (a temperature where 50% of antiferromagnetic martensite transformed to paramagnetic martensite), was associated with antiferromagnetic-paramagnetic transition characterised by Néel temperature ( T N ) [16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the present authors pointed out that, in MA'ed Fe–Mn–Si–Cr–Ni SMAs, a second internal friction maximum occurs during heating. This tan δ maximum, located at a temperature (a temperature where 50% of antiferromagnetic martensite transformed to paramagnetic martensite), was associated with antiferromagnetic-paramagnetic transition characterised by Néel temperature ( T N ) [16].…”
Section: Methodsmentioning
confidence: 99%
“…One peculiarity of PM FeMnSi-based SMAs is the formation of large amounts of α ′ -bcc thermally induced martensite [15]. The presence of α ′ was associated with large levels of internal friction [16] which experienced an increasing trend together with the pre-straining degree and the MA'ed fraction [17]. The amount of α ′ increased additionally with the number of mechanical cycles [18], the volume fraction of MA'ed powder [19] and pre-straining degree, except for the specimens ST'ed at 1273 and 1373 K [20].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of thermally induced α -bcc martensite was revealed, as a particularity of these P/M-MA'ed alloys. Martensite plates became finer with the increase of MA'ed fraction, which enhanced a global increasing tendency of the amount of α -bcc martensite on behalf of the amount of γ-fcc austenite (Mihalache et al, 2015). It has been concluded that internal friction, determined statically and dynamically, experienced an increasing trend with prestraining degree, heat treatment temperature and MA'ed fraction (Mihalache et al, 2017).…”
Section: Thermomechanical Processing and Pre-straining Effectsmentioning
confidence: 96%
“…When Fe-SMA is employed as a measure of prestressing, the amount of prestress is the property of most concern to engineers. With the aim of increasing the shape recovery properties, many research groups across the world have been devoted to developing improved production and manufacturing processes, including but not limited to thermal mechanical training, adjusting the chemical compositions and heat treatment [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. These efforts greatly enhance the reliability of Fe-SMA as an emerging prestressing strategy.…”
Section: Basic Propertiesmentioning
confidence: 99%